Thymidylate synthase enhancer region: Novel allele in Indians - Dipali Dhawan; Harish Padh (Taylor & Francis Group, 2017)
Background: Thymidylate synthase (TS) is the major target for fluoropyrimidine drugs like 5-Fluorouracil (5-FU). There are polymorphic tandem repeats in the TYMS gene enhancer region (TSER). The number of tandem repeats varies in different populations. The aim of this study was to determine the frequencies of the TSER tandem repeats (rs34743033) and compare the observed frequencies with those of other populations. Methods: This study genotyped 350 healthy individuals by Polymerase Chain Reaction (PCR). Results: A novel allele *1 (only a single repeat) was observed in four individuals, the individuals were heterozygous (TSER*1/*2) for TYMS. Another variant rs2853542 affecting the expression of Thymidylate synthase was also analysed. The observed genotype frequencies were compared with frequencies observed in other populations for understanding differences between various population groups. There was a statistically significant difference between Indians and Chinese, Kenyans, Ghanians, African-Americans, Americans of European Ancestry, British, Hungarians, Turkish, Australians and Brazilians. Conclusion: This study identified a novel single repeat in the TYMS gene which might have an impact on the expression of this gene, which needs to be confirmed by functional studies.